Baba na swieczniku - Letowska, Ewa.; Janicki, Mariusz; Podemski, Stanislaw (Warszawa : Polska Oficyna Wydawnicza BGW, 1992)
An interview with the first woman advocate for civil rights in Poland.
Keywords: Letowska, Ewa -- Interviews; Women civil rights workers -- Poland -- Interviews; Civil rights -- Poland; Poland -- Politics and government -- 1980-1989.; Poland -- Politics and government -- 1989-